The role of solvation effects in the growth of TCNQ-based charge-transfer salts - Rösner, Benedikt; Späth, Andreas; Fink, Rainer (Journal of Crystal Growth, 2013)
Combining various microscopic techniques (VLM, SEM, STXM) we were able to investigate the growth TCNQ-based charge transfer salts nanocrystals in the wet chemical route. The results unambiguously show the impact of diffusion processes on the formation of Ag-TCNQ nanocrystals to support a modified mechanism for crystal formation. TCNQ-based charge transfer salts represent an attractive class of materials for utilisation in nanoscaled electronic devices. Detailed knowledge about the formation of metal-TCNQ salts is essential to control the growth of well-defined nanostructures. Silver template patterns were used to define well-ordered Ag-TCNQ structures. A comprehensive microscopic and spectroscopic investigation was conducted to examine the growth mechanism in wet-chemical environment in detail. Scanning electron microscopy (SEM) disclosed the overall morphology of the fabricated nanostructures while Scanning Transmission X-Ray Microscopy (STXM) provided insight into the chemical behaviour of the metal cation during the growth. The experimental results give clear evidence that solvation and diffusion of the metal counter ions controls the growth of well-defined metal-TCNQ nanocrystals. © 2013 Elsevier B.V. All rights reserved.